(untitled) (Plant Bulletin, 2025)
Star Channa, a newly introduced desi chickpea cultivar, is known for its high yield potential, large seed size, and built-in resistance to key chickpea diseases such as Fusarium wilt and Ascochyta blight. It received approval in 2021 from the Punjab Seed Council for widespread cultivation in irrigated and rain-fed areas of Punjab, Pakistan. The variety was evolved through artificial hybridization between female parent 98004 and male parent 5A015, utilizing bulk and pedigree methods of plant selection during various stages of breeding at the Arid Zone Research Institute in Bhakkar, Punjab, Pakistan. The selected line was tagged as TG1305 and then included in a series of yield assessments, pathological, entomological, and agronomic trials. Star Channa demonstrated a commendable average yield potential ranging from 3800 to 4000 kg/ha. It takes 88-90 days to reach 50% flowering and 138-145 days to reach 90% pod maturity. The seed size is bold, while seeds per pod ranged from 01 to 02. It has a 100-seed weight of 29-30 g, the number of pods per plant ranges from 75 to 80, the plant height is 65-68 cm, and the grain color is brown. As far as the quality is concerned, the protein percentage is high enough (23.9%) with desirable ash (3.63%) and crude fat contents (3.72%). It exhibited good yield potential when cultivated during October by maintaining a seed rate of 75 kg/ha and a fertilizer dose of 23-57-00 NPK kg/ha. In essence, Star Channa (TG1305) represents itself as a resilient and disease-resistant cultivar evolved to flourish in diverse environments and contribute to a sustainable farming system.